Ownership Concentration and Earning Quality: Moderating Role of Board Diversity - Triyonowati Triyonowati; Rizki Amalia Elfita; Titik Mildawati; Ikhsan Budi Rihardjo; Suwitho Suwitho (AKRUAL: JURNAL AKUNTANSI, 2022)
Bad management practices that occur in the industry cause a lot of harm to many parties. Bad management practices occur due to managers' efforts to manipulate profits. Bad management practices that are carried out by management will be aggravated if the majority of shareholders participate to press the managers to make a profit manipulation so the earning quality becomes low. The purpose of this research is to find out how ownership concentration affects earnings quality and to determine the ability of directors to reduce the influence of ownership concentration on income quality. The research data used is a manufacturing company registered with the IDX in 2019-2020 with sampling methods using the target population method, that is, a sample determination technique using certain considerations. The data analysis method used is Moderated Regression Analysis (MRA). The results proved that the ownership concentration negatively affects the earning quality and board diversity can moderate the influence of ownership concentration on earning quality. Test results show that Board Diversity can reduce the behavior of Ownership Concentration in performing earnings manipulation